REPRODUCTIVE ECOLOGY OF EASTERN WILD TURKEY FEMALES IN THE EASTERN MISSOURI OZARKS - Larry D. Vangilder; Michael W. Hubbard; David A. Hasenbeck (Wildlife Society Bulletin)
Abstract: We studied reproductive ecology of radiomarked eastern wild turkey (Meleagris gallopavo silvestris) females in the eastern Ozarks of Missouri on 2 study areas during 1990–98. Across years and study areas, nesting rates ranged from 45.3 to 100%. Nest success of females that did attempt to nest ranged from 14.1 to 63.3%. Survival of poults to 4 weeks of age ranged from 0 to 82%. Even though the 2 study areas were only about 30 km (19 mi) apart, differences in nesting rate between areas were detected. On both study areas, nesting rate of juveniles was lower than that of adults. When compared with data from radiomarked females in northern Missouri, nesting rates, female success, and poult survival in the eastern Ozarks were substantially lower. Average reproductive rates were much lower in the eastern Ozarks than in northern Missouri and do not appear to be sufficient to maintain population levels observed at the beginning of the study.